Psychopathology in Sri Lankan patients with first-episode psychosis - Balasooriya, N.S.; Wijesiri, H.G.V.W.; Hanwella, Raveen; De Silva, V. (Sri Lanka Journal of Psychiatry, 2017)
Background: First episode psychosis (FEP) is the first episode of a psychiatric illness with psychotic symptoms. Delay in diagnosis increases the duration of untreated psychosis (DUP) and leads to poorer outcome. Aims: To explore the psychopathology of patients with FEP presenting to the National Hospital of Sri Lanka (NHSL). Methods: This was an observational descriptive study. Patients admitted to ward-59, NHSL from March 2012 to November 2013 who met inclusion criteria were considered for the study. Data was collected retrospectively from bed head tickets using a structured questionnaire. Results: The sample size was 101, of which 57 were male. A majority of the participants were in the 13-26 year age group. Delusions were the most common psychopathology noted in this sample, with persecutory themes being the most common content. Of the hallucinations, second person auditory hallucinations were the commonest type. Non-euthymic mood was seen in over two-thirds of participants, with depressed mood being the most common finding. Insight was poor in over half the participants. Schizophrenia was the most common diagnosis noted in this group of patients, followed by mania with psychotic features. Conclusions: Persecutory delusions, second person auditory hallucinations, mood and speech abnormalities were prominent among participants of this study. A better understanding of psychopathology in FEP may help to reduce DUP.
Keywords: First episode psychosis; Psychopathology; Sri Lanka